2011
DOI: 10.1002/bsl.991
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness, Criminal Risk Factors and Parole Release Decisions

Abstract: Research has not examined whether higher rates of parole denial among inmates with mental illness (MI) are the result of the increased presence of criminal risk factors among this population. Employing a representative sample of inmates with (n  =  219) and without (n  =  184) MI receiving parole release decisions in 2007, this study tested whether the central eight risk factors for recidivism considered in parole release decisions intervened in the relationship between MI and parole release. MI was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…With the disproportionate representation of mentally ill in prison, concern about the economic and social consequence of this growing population has led to a vast wealth of research. However, our understanding of mental health status as an independent contributor to parole decision making is both limited and mixed (see [71] 2011 for a more thorough review of the empirical evidence). To provide more insight into this largely unexamined area of parole decision making, we examined specific mental health indicators for their unique contribution in parole decision making net the effects of other factors explaining variation in parole decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the disproportionate representation of mentally ill in prison, concern about the economic and social consequence of this growing population has led to a vast wealth of research. However, our understanding of mental health status as an independent contributor to parole decision making is both limited and mixed (see [71] 2011 for a more thorough review of the empirical evidence). To provide more insight into this largely unexamined area of parole decision making, we examined specific mental health indicators for their unique contribution in parole decision making net the effects of other factors explaining variation in parole decisions.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to mental health and its impact on parole, the research is limited, and findings have been inconsistent; some studies found inmates with mental health problems are less likely to be paroled than nonmentally ill inmates [68,69], while others that mental health issues do not appear to impact parole decision making [70,71]. Caplan [56] (2007) conducted a review of the existing literature and found mental health status to have a negative impact on parole decisions and also to be one of the main influential factors on parole decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inmate performance upon release has received significant attention recently (e.g., Berg and Huebner 2011;Gunnison and Helfgott 2011;Hipp et al 2011;Mallik-Kane and Visher 2008;Naser and Vigne 2006;Schlager and Robbins 2008;Zhang et al 2006;Zgoba et al 2008), such research efforts have not attempted to link studying of parolee performance to parole decisionmaking, as the current study did. As for the parole decision itself, it has been largely neglected in the contemporary criminal justice literature, with only a handful of studies addressing possible determinants and underlying processes (Caplan 2007(Caplan , 2011Hannah-Moffat and Yule 2011;Huebner and Bynum 2008;Matejkowski et al 2011;Morgan and Smith 2008;Roberts 2009). Lastly, the current research also contributes evidence related to other, broader themes in the criminological and criminal justice literature.…”
Section: Introductionmentioning
confidence: 85%
“…The majority of extant work on parole decisions is quantitative, documenting the factors correlated with parole outcomes, including inmate race, mental illness, and in‐prison behavior (e.g., Matejkowski et al 2011; Mooney and Daffern 2014; Morgan and Smith 2008; Weisberg, Mukamal, and Segall 2011; Young, Mukamal, and Favre‐Bulle 2016). A few notable exceptions examine hearings' social dynamics from a qualitative perspective.…”
Section: Introductionmentioning
confidence: 99%